ADAPTATION AS A BASIC DETERMINANT PERSONAL SELF-CONSTRUCTION OF THE PERSONNEL OF ORGANIZATIONS - Solomka, Tamara (PSYCHOLOGICAL JOURNAL, 2018)
The article analyses the main theoretical and methodological approaches to the phenomenon of adaptation and defines the state of its study as the basic determinant of personal self-construction of the personnel of organizations (PS-CPO). Some aspects of the adaptation problem as the main determinants (PS-CPO) in the views of foreign scientists are presented: in the measurement of the reflection of self-construction, the ideological practical contexts of constructs, "the daily routine of personnel", the identification of aspects, functions and stages of adaptation in organizations. Organizational adaptation can be considered as an integration of an individual into a new sphere of his future existence that was unknown earlier, with subsequent awareness, assimilation and use of the organizational scenario (production standards), as well as his own role in it. It is emphasized that adaptation in procedural and effective expression is a way to reverse the challenges of a new (unknown until now) for the chance to design an exclusive model (PS-CPO). At the same time, all the most important components of the PS-CPO process are specific adaptive innovations: definitions, specific measuring interpretative procedures in the unity of the development of the individual and the elements of the structure of the organization. It is emphasized that subjectively personal self-construction in the process and in the result of adaptation is an internalized form of expansion of the individual consciousness, which relies on the creative meeting of the person with itself (for example, what it really is), for building oneself as she would like to be. Generalized use of the "proprietary" approach of G. Allport in the definition of the conceptual apparatus of adaptive characteristics of the subject PS-CPO. The subjectivity of the PS-CPO is a function that rises over other pro-active functions and synthesizes them. The result of this process is the ability to self-knowledge and self-design of personnel. The definition of the notion of adaptation as a basic determinant of the PS-CPO, which assumes the presence of an open nonlinear system with a significant level of complexity with respect to development and constructive productivity, is substantiated. A significant difference from other complex nonlinear systems lies in its controllability not only by external circumstances, but also by an internal factor-the person who carries such a system. It is pointed out the need for a positive psychological pattern and sustainable development of the organization, which must deal with the successful implementation of adaptation, as well as personal well-being and the possibility of developing the internal potential of its main character-personnel.